Exports and Economic Growth long Run Relation in Africa Countries - (:unkn) unknown (My University, 2025)
The aim of this study is to analyze the effect of export economic growth in long run for Africa countries, controlling for foreign direct investment and gross fixed capital formation using panel cointgeration framework. The panel unit root test showed a mixture of integration order, which implies panel ARDL cointgeration test is the appropriate technique for cointegration test. The seven panel cointegration test indicates the presence of a cointgeration relationship in the panel. Generalized method of moments (GMM) technique indicates error correction term being negative and significant in 16 countries at 5% and 10%. In the long run, export and gross fixed capital formation have a positive effect on economic growth while foreign direct investment has a negative effect. The panel causality test shows the existence of a bi-directional causal flow in the following relations; economic growth-export, export-foreign direct investment, foreign direct investment-gross fixed capital formation, gross fixed capital formation-export. Economic growth does not granger cause foreign direct investments and gross fixed capital formation. African countries need to formulate policies that will enhance international trade specifically exports, either within the continent and worldwide. At the same time, support to African countries from developed economies and international institutions should aim to maximize the potential in export trade.
Keywords: African Research